Evaluating the Impact of Gender Quotas on Women’s Political Participation and Empowerment in Post-Federal Nepal - Ghalan, Ramila; Mishra, Bal Chandra (Journal of Advanced Academic Research, 2026)
The paper analyses how gender quotas affect women political representation and empowerment in post-federal Nepal since 2015, which provides one-third female representation in federal and provincial legislatures and 40 percent in locally based on the Constitution of 2015. Though since the 2017 and 2022 elections, women have become more descriptively represented under these provisions, there is debate over whether they can create the empowerment of women substantively especially in the rural and remote setting where patriarchy influences. Based on Feminist Institutionalism, the study also conceptualizes the political institutions within a gendered space in which it coexists with formal rules like quotas and more informal practices that limit the agency of women. By using an integrated approach of convergent parallel design, the study will be based on quantitative and qualitative data of 120 elected Nepalese women representatives in the three ecological regions of the country through surveys, interviews, focus group discussions and key informant interviews and analyzed through descriptive statistics and thematic analysis. The results demonstrate that socio-cultural factors and institutional factors (such as not being included on important committees, inadequate training, insufficient party support and bureaucracy) are preventing women to exercise their political agency, and are hindering exercise of agency, nonetheless, further centers on institutional factors prevent women. It implies that this research has found that gender quotas act as the entry mechanism, but substantial empowerment mandates an institutional overhaul and expansion of the socio-cultural transformation.